A formalização da relevância da questão federal no recurso especial - Silva, Roberta Scalzilli (2014)
This study aims to analyze the relevance of the institute federal question presented by the Proposed Constitutional Amendment nº. 209/2012, in the National Congress, as a new admissibility requirement of Special Resource. First demonstrate is historical and general aspects of the resource and its court of origin, the Superior Court of Justice. Following is for the examination of the judgment of admissibility and some procedural issues that permeate the extraordinary instance. This paper approach highlighting the impact of the general repercussion used in Extraordinary Resource as an access filter to the Supreme Court , which serves as a paradigm for this search. With this, we draw a parallel between the old argumentation of relevance federal question, the current system of general repercussion and relevance of the federal issue projected to the Special Resource, examining the main characteristics of each filter mechanism. Finally, after considerable reflection on the losses and efficiencies of the institute to the legal system, it is verified that the introduction of this contention access to the Superior Court of Justice shall thrive because this Court able to bring their original function as primarily protect the public interest over private, which should only occur reflexively in trials of exceptional resources.